Neonatal Abusive Head Trauma without External Injuries: Suspicion Improves Diagnosis - Seokwon Yoon; Juyoung Lee; Yong Hoon Jun; Ga Won Jeon (MDPI AG, 2022)
The term "shaken baby syndrome" has been replaced by "abusive head trauma (AHT)" based on the mechanism of injury. The reported mortality rate of AHT ranges from 10% to 30%. Up to two-thirds of survivors suffer from serious long-term disabilities. Thus, an expeditious and accurate diagnosis is crucial to prevent further abuse that might result in death or serious disabilities. It remains a challenge for physicians to diagnose AHT when parents do not give a history of trauma in preverbal infants without any external signs. Here, we report a case of a 14-day-old boy who presented with a febrile convulsion without evident external injuries nor history of trauma according to his parents. He was diagnosed with AHT based on MRI findings of subacute subdural hemorrhage, multiple cortical hemorrhages, cerebral edema, and diffuse axonal injury. In conclusion, health care providers should keep in mind that the history of trauma provided by the parents or caregivers might not always be true and that reasonable suspicion of abuse is the most important in the diagnosis of AHT, although neuroimaging plays a pivotal role. Reasonable suspicion of AHT in combination with a thorough physical examination, neuroimaging, and skilled neuroradiologist can improve diagnosis and help victims in a timely manner.